Digital transformation as the main condition for the development of modern higher education - Tetiana Sych; Yevhen Khrykov; Olga Ptakhina (Academy of Cognitive and Natural Sciences, 2021)
The article considers the potential and limitations that arise in the higher education system as a result of the e-technology use. E-learning has become an integral part of the 21st century education system. The pace of dissemination and implementation of e-technologies in all spheres of public life, in science and education in particular, is constantly growing. There are different views in the scientific community and the public on the digital transformation of education. However, with the entry into our lives of COVID-19, the use of e-technologies in education ceases to be a matter of innovation, and becomes a vital necessity for the functioning of the educational system and the activities of educational institutions. Analysis of more than 50 concepts that characterize the modern education system, educational technologies and the process of digital transformation of education allowed the authors to draw conclusions about the importance of information technology in education and the main trends in their development. The article also summarizes the different views of scientists on the digital transformation of higher education, the use of e-technology in the educational process. The advantages that e-technologies provide to the educational process and the challenges of their use that need to be addressed are outlined. The study of the experience of the leading universities of Ukraine allowed the authors to draw conclusions about the state of digital transformation of higher education in Ukraine. Elaboration of scientific literature, own observations and research have allowed to define the tendencies of development of higher education in the epoch of digital transformation.